TAX REFORM OF INCOME TAX IN PERU 1936-2009 - García Castro, Ricardo (2010)
All the tax reforms of income tax, have been significantly prosecutors that were not taken into account economic, social and financial and taxation serve to the country’s development. Generally the tax rules have been developed without the full knowledge of the reality of our country. The procedures we followed in this investigation has been to locate books, magazines, press releases, brochures and newspapers, specialist consultations of the item. The result of this research are that to make a comprehensive tax reform should be considered a reform of the State.